Comparison of Remnant-Preserving Augmentation and Double-Bundle Reconstruction for Partial Anterior Cruciate Ligament Tears - Wutphiriya-angkun, MD, Sombun (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The most effective method for the surgical treatment of partial anterior cruciate ligament tears has not been definitively established. Two commonly used techniques are remnant-preserving augmentation and double-bundle reconstruction. This retrospective study was conducted to test the hypothesis that clinical outcomes are similar with the two methods. Methods: A total of 43 patients who had been treated for partial anterior cruciate ligament tears by either remnant-preserving augmentation or double-bundle reconstruction were included. Twenty-one patients were treated with remnant-preserving augmentation and 22 were treated with double-bundle reconstruction. Patient data collected included preoperative and postoperative range of motion, visual analog scale, Lysholm Knee Scoring, International Knee Documentation Committee Knee Evaluation Form scores, anterior drawer test, Lachman test and pivot-shift test. Results: There were no significant differences in postoperative range of motion, visual analog scale score, Lysholm score or International Knee Documentation Committee knee evaluation form score between the two groups (P > .05). The pivot-shift test was significantly better in the remnant-preserving augmentation group than the double-bundle reconstruction group (P = .040); however, there was no significant difference between the two groups in either the anterior drawer test or the Lachman test (P > .05). Conclusions: The effectiveness of remnant-preserving augmentation is comparable to double-bundle reconstruction in the treatment of partial anterior cruciate ligament tears in terms of anterior and rotary stability and clinical scores.